2010
DOI: 10.1016/j.jcis.2009.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Capillary rise between parallel plates under dynamic conditions

Abstract: A Lattice-Boltzmann method based on field mediators is proposed to simulate the capillary rise between parallel plates by considering the effect of long-range interactions between the fluids and the solid walls. As a starting point, a liquid-vapor system was employed, which was modeled using a known model described in the literature. The simulations were compared with theoretical solutions of the Bosanquet equation. The results obtained are in good agreement with theoretical predictions, particularly when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 48 publications
(81 reference statements)
0
20
1
Order By: Relevance
“…The major assumption used in (1.2) is the constancy of the contact angle θ. The studies of dynamical wetting (Hoffman 1974;Tanner 1979;de Gennes 1985) later showed that this is generally not the case, so that the Lucas-Washburn law must be corrected in the first steps of the rise (Siebold 2000;Wolf 2010). Another assumption in this law is that inertia is negligible.…”
Section: Introductionmentioning
confidence: 99%
“…The major assumption used in (1.2) is the constancy of the contact angle θ. The studies of dynamical wetting (Hoffman 1974;Tanner 1979;de Gennes 1985) later showed that this is generally not the case, so that the Lucas-Washburn law must be corrected in the first steps of the rise (Siebold 2000;Wolf 2010). Another assumption in this law is that inertia is negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the diversity of actual porous media, the √ t scaling law, which results macroscopically from the balance between a constant driving capillary force and an increasing viscous drag, is ubiquitously observed. In fact, it appears that the LW relationship holds down to the nanoscopic scale, as shown by recent experimental 10,11 and theoretical studies [13][14][15][16][17][18] . This of course is an important indication for the development of nanofluidic devices.…”
Section: Introductionmentioning
confidence: 90%
“…In the literature, capillary rise simulations using the lattice Boltzmann method have been performed ( Latva-Kokko and Rothman, 2005b;Raiskinmäki et al, 2002;Wolf et al, 2010 ). These simulations considered Bond numbers = 10 −1 − 10 0 based on the definition of Eq.…”
Section: Capillary Rise Simulationmentioning
confidence: 99%